Phage treatment of multidrug-resistant bacterial infections in humans, animals, and plants: The current status and future prospects - Omor Faruk; Zilhas Ahmed Jewel; Sanjoy Bairagi; Mohammad Rasheduzzaman; Hindol Bagchi; Akber Subahan Mahbub Tuha; Imran Hossain; Ayon Bala; Sarafat Ali (Infectious Medicine, 2025)
Phages, including the viruses that lyse bacterial pathogens, offer unique therapeutic advantages, including their capacity to lyse antibiotic-resistant bacteria and disrupt biofilms without harming the host microbiota. The lack of new effective antibiotics and the growing limitations of existing antibiotics have refocused attention on phage therapy as an option in complex clinical cases such as burn wounds, cystic fibrosis, and pneumonia. This review describes clinical cases and preclinical studies in which phage therapy has been effective in both human and veterinary medicine, and in an agricultural context. In addition, critical challenges, such as the narrow host range of bacteriophages, the possibility of bacterial resistance, and regulatory constraints on the widespread use of phage therapy, are addressed. Future directions include optimizing phage therapy through strategies ranging from phage cocktails to broadening phage host range through genetic modification, and using phages as vaccines or biocontrol agents. In the future, if phage can be efficiently delivered, maintained in a stable state, and phage–antibiotic synergy can be achieved, phage therapy will offer much needed treatment options. However, the successful implementation of phage therapy within the current standards of practice will also require the considerable development of regulatory infrastructure and greater public acceptance. In closing, this review highlights the promise of phage therapy as a critical backup or substitute for antibiotics. It proposes a new role as a significant adjunct to, or even replacement for, antibiotics in treating multidrug-resistant bacterial infections.